DILEMA KONSUMEN MAHASISWA TADRIS IPS UIN SIBER SYEKH NURJATI CIREBON DALAM MEMILIH PRODUK RAMAH LINGKUNGAN: ANALISIS FAKTOR PENENTU DALAM PERSPEKTIF EKONOMI ISLAM - Shufiyyati, Shufiyyati; Herti, Navila Laela; Pratama, Andika Septy (CV. Kalimasada Group, 2025)
This study aims to investigate the factors influencing the consumer dilemma of Tadris IPS students at UIN Siber Syekh Nurjati Cirebon in choosing environmentally friendly products. Employing an observational method using interviews and an Islamic economics framework, data was collected through in-depth interviews with 5 students. The results indicate that the most significant factors influencing consumer dilemma are price, product availability, and personal values. Islamic economic principles, such as tawhid (unity of God), khilafah (stewardship), and adl (justice), were found to moderate the relationship between these factors and the environmental dilemma. The study concludes that addressing the environmental dilemma requires a holistic approach that considers consumer behavior, product availability, and Islamic economic principles.